2018
DOI: 10.1074/mcp.ra117.000096
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Profiling of N-linked Glycosylation Machinery in Yeast Saccharomyces cerevisiae

Abstract: Asparagine-linked glycosylation is a common posttranslational protein modification regulating the structure, stability and function of many proteins. The -linked glycosylation machinery involves enzymes responsible for the assembly of the lipid-linked oligosaccharide (LLO), which is then transferred to the asparagine residues on the polypeptides by the enzyme oligosaccharyltransferase (OST). A major goal in the study of protein glycosylation is to establish quantitative methods for the analysis of site-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 69 publications
0
40
0
Order By: Relevance
“…Recently, N-glycoproteomics studies have been performed in the tissues of different organisms, including yeast [47][48], filamentous fungi [49][50], nematode [51], Drosophila [52], the plant Arabidopsis thaliana [53] and mammals [54][55][56]. Quantifying the N-glycoproteomes in the plant pathogenic fungus F. graminearum have revealed intensive glycosylation changes during exposure to fungicide: 774 sites in 406 proteins were identified, and the glycosylation level was found to be largely down-regulated upon fungicide treatment [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, N-glycoproteomics studies have been performed in the tissues of different organisms, including yeast [47][48], filamentous fungi [49][50], nematode [51], Drosophila [52], the plant Arabidopsis thaliana [53] and mammals [54][55][56]. Quantifying the N-glycoproteomes in the plant pathogenic fungus F. graminearum have revealed intensive glycosylation changes during exposure to fungicide: 774 sites in 406 proteins were identified, and the glycosylation level was found to be largely down-regulated upon fungicide treatment [50].…”
Section: Discussionmentioning
confidence: 99%
“…To generate GFP-fused constructs, the promoter and coding regions of Gls1 was amplified and fused with GFP, then cloned into pKN(S6 Table). In the resulting vectors, the GFP fusion constructs were expressed under the control of the native promoter [48]. These vectors were transformed to protoplasts of P131, the Δalg3 mutant or the Δgls1 mutant to obtain the GFP-tagged strains.…”
Section: Western Blottingmentioning
confidence: 99%
“…To identify sequence motifs that were generally associated with N-glycosylation sites, we examined a 21-amino acid sequence window surrounding the central Nglyco residues of each site using the web-based Motif-X program with a significance threshold of P < 0.000001. Previous research showed that the consensus sequence for N-glycosylation motif is Nglyco-X-S/T (X P) (10)(11)(12)(13). In this study, we found that most of the 248 N-glycosylation sites matched the Nglyco-X-S/T motif ( Fig.…”
Section: N-glycosylation Preferentially Located On Five Conserved N-gmentioning
confidence: 99%
“…Then, the oligosaccharyltransferase (OST) catalyzes the en bloc transfer of the LLO to the asparagine side chain of the acceptor polypeptides in the ER lumen (9,10). The OST selects polypeptides carrying an Nglyco-X-S/T (X P) motif and generates the N-glycosidic linkage between the side chain amide of asparagine and the LLO (9)(10)(11)(12). Moreover, other conserved N-glycosylation motifs have been identified through liquid chromatography -tandem mass spectrometry (LC-MS/MS).…”
Section: Introductionmentioning
confidence: 99%
“…Oligosaccharyltransferase (OTase) catalyzes the attachment of the precursor oligosaccharide to selected Asn residues in glycosylation sequons (N-X-S/T; X¹P) in nascent polypeptides [14]. Mutations in ALG genes can cause altered glycan structures due to the accumulation and transfer of truncated glycans, and altered site-specific glycan occupancy due to inefficient transfer of these truncated glycans by OTase [15,16]. Further trimming and maturation of glycans take place in the ER and Golgi with various enzymes involved, leading to diverse N-glycan structures on mature glycoproteins [17,18].…”
Section: Introductionmentioning
confidence: 99%